Shajarat al-mulūk : Tārīkh-i manẓūm-i Sīstān az kuhantarīn rūzgārān tā farmānrawāyi-yi Malik Bahrām-i Kiyānī dar dahihā-yi nukhust-i ḥukūmat-i Qājārān - Ṣabūri (Miras Maktoob, ISBN: 9789004365452., 2019)
Sistan is a region straddling the eastern border between Iran and Afghanistan and on the Iranian side part of the province of Sistan-Baluchistan. Irrigated by numerous rivers coming from the mountains of central Afghanistan, the fields of Sistan produce mostly barley and wheat. Located on the trade routes between north and south and east and west, Sistan's strategic importance has always been recognized. The last conflict involving control over Sistan dates back to the nineteenth century when Persia and Afghanistan disputed the region, the border finally being fixed by the second Sistan Border Commission in 1903-05. There are not many local histories on Sistan, until recently only the anonymous Taʾrīk̲h̲-i Sīstān (5th-7th/11-13th cent.) and Malik Shāh Ḥusayn's Iḥyāʾ al-mulūk (11th/17th century). The history of Sistan published here is especially interesting because it runs until the beginning of the nineteenth century. Until now, we possessed little information beyond the early eighteenth century. Mathnawī, imitating the Shāh-nāma.